Inhibition of Carbon Steel Corrosion by Some New Organic 2-Hydroselenoacetamide Derivatives in HCl Medium - Alaa Abdel Khaleq Khalib; Hanan Abdul Jaleel Al-Hazam; Attared Fadhel Hassan (Universitas Gadjah Mada, 2022)
This study aims to prepare 2-hydroselenoacetamide derivatives (5-8) to use some of these compounds as corrosion inhibition for carbon steel in 1 M HCl. The compound C10H10NO2Cl 1 was prepared by reacting between p-aminoacetophenone with chloroacetyl chloride, and then reacted 1 with substituted benzaldehyde to obtain the corresponding derivatives as C17H13N2O4Cl 2, C18H16NO4Cl 3 and C19H18NO4Cl 4. The last step in this study was conducted to obtain the organic hydroselenoacetamide such as C10H11NO2Se 5, C17H14N2O4Se 6, C18H17NO4Se 7, and C19H19NO4Se 8 by reacting chloroaminochalcone and sodium hydrogen selenide. All compounds were characterized by Fourier Transform Infrared Spectroscopy (FTIR), proton nuclear magnetic resonance (1H-NMR), and elemental analysis (CHN). The corrosion inhibition activity of C17H14N2O4Se 6, C18H17NO4Se 7 and C19H18NO4Cl 4 for carbon steel in 1 M HCl solution was investigated by using weight loss methods and electrochemical study. The activation energy of the corrosion reaction was also calculated. The effect of different concentrations and temperatures on inhibition efficiency was investigated. The results showed that the corrosion rate decreased with the increase of the concentration of inhibitors, while the inhibition efficiency and covered area decreased with an increase in the temperature. Polarization studies demonstrated that the inhibitors were of mixed type. The purpose of this study was to prepare, characterize and evaluate the corrosion inhibition activity of hydroselenide compounds for carbon steel in 1 M HCl.